STRATEGI PENGEMBANGAN INDUSTRI SERAT ALAM DAUN NANAS UNTUK MENINGKATKAN TARAF HIDUP MASYARAKAT - Asmanto Subagyo (Asian Journal of Innovation and Entrepreneurship, 2012)
Intense competition from synthetic fibers has affected the production of natural fibers all over the world. Of the total global fiber production of 50,88 million tones, according to annual report available for the year 2007 natural fiber contributed about 57%. This share came down further 52% in 2008 and since 2009 increases significantly. Empowerment of social economic program must be able to conduct public economy which based at country town. These programs must be able to achieve seven goals, such as net export income and rising public income; founding industrial structure based on the strength of small-medium enterprises; founding the foundation of economic transition to industrial age by developing forces of agro-industrial and agribusiness; achieving global competitive advantage by increasing productivity; innovation; and effective (appropriate technology) dissemination; increasing quality(global standards); creating high economic activity and keep sustainable quality environment. Natural fiber (pineapple leaf) industry is one of Indonesia is industrial sector which was identified having the ability to achieve these goals. Several reasons are pointed out, such as that Indonesia has greatest agro-fiber planted areas the for example pineapple, agave(sisal),ramie, kenaf and henemp, so that for the future Indonesia will get 10% natural fiber production share in the world. So that the National Natural Fiber Industry has strategic position and high prospect will be developed at the future. This paper present discuss and describe to support The Indonesian Natural Fiber Industry Development Program, such as mapping Natural Fiber Development areas based on the potency of natural fiber (agro-fiber) production and planted area; analysis of industrial scales, structure of industrial development and feasibility study. Finally, this paper describe state industry of natural fiber development strategy and stated strategy recommendation to stakeholders. Keywords: agro-fiber, empowering, natural fiber industry, appropriate technology, pineapple